Politik Hukum dalam Penyelesaian Sengketa terhadap Kepemilikan Hak Atas Tanah - Ismaidar Ismaidar; Tamaulina Br. Sembiring; Yoldy Israq (Lembaga Pengembangan Kinerja Dosen, 2025)
The issue of land ownership disputes is a complex issue and often triggers prolonged conflicts in Indonesia. Land disputes can be caused by various factors, such as overlapping certificates, illegal land control, and weak law enforcement. In this context, legal politics becomes an important instrument in formulating policies to resolve land disputes fairly and efficiently. This paper aims to analyze the role of legal politics in resolving land ownership disputes, identify obstacles in policy implementation, and offer solutions to increase the effectiveness of dispute resolution. The research uses a normative approach with analysis of statutory regulations, official documents and academic literature. The research results show that existing regulations, such as the Basic Agrarian Law no. 5 of 1960, requires harmonization with other policies to overcome overlapping regulations. In addition, the role of mediation and arbitration institutions is considered crucial in reducing the burden on courts. However, weak legal dissemination to the community is a significant obstacle in policy implementation. This paper recommends strengthening regulations, increasing the capacity of mediation institutions, and legal education to the community as strategic steps to create a more effective land dispute resolution system.